Positive and Negative Earnings Surprises, Regulatory Climate, and Stock Returns* - NWAEZE, EMEKA T. (Contemporary Accounting Research, 2000)
This study focuses on electric utilities in the United States to consider two related issues. First, the study tests for asymmetric price reactions to positive and negative earnings surprises (ES). Second, the study associates policy differences across jurisdictions with variations in the cash flow effects of positive and negative ES and then uses the framework to consider variations in price responses across regulatory climates. In the same context, the study investigates the effects of a utility's abnormal profits on the asymmetry of price reactions to positve and negative ES. The empirical predictions are motivated by the disparity between the principles and practices that underlie cost recovery for the utilities and the uneven effects of the cost‐recovery practies on the cash flows associated with positve and negative ES. The results show that the sign of ES and the climate in which a utility operates are related to the size of price reactions to ES. Furthermore, a utility's abnormal profit status has significant effects on the size of price reactions to ES. Only a modest price response asymmetry is indicated for manufacturing firms.